AFM, ESEM, TEM, and CLSM in liposomal characterization: a comparative study - Barbara Ruozi (Dove Medical Press, 2011)
Barbara Ruozi1, Daniela Belletti1, Andrea Tombesi2, Giovanni Tosi1, Lucia Bondioli1, Flavio Forni1, Maria Angela Vandelli11Department of Pharmaceutical Sciences, University of Modena and Reggio Emilia, Modena, Italy; 2C.I.G.S., University of Modena and Reggio Emilia, Modena, ItalyAbstract: An outstanding aspect of pharmaceutical nanotechnology lies in the characterization of nanocarriers for targeting of drugs and other bioactive agents. The development of microscopic techniques has made the study of the surface and systems architecture more attractive. In the field of pharmaceutical nanosystems, researchers have collected vital information on size, stability, and bilayer organization through the microscopic characterization of liposomes. This paper aims to compare the results obtained by atomic force microscopy, environmental scanning electron microscopy, transmission electron microscopy, and confocal laser scanning microscopy to point out the limits and advantages of these applications in the evaluation of vesicular systems. Besides this comparative aim, our work proposes a simple confocal laser scanning microscopy procedure to rapidly and easily detect the liposomal membrane.Keywords: atomic force microscopy, transmission electron microscopy, environmental scanning electron microscopy, confocal laser scanning microscopy